Digressive Voices in Early Modern English Literature. - Cotterill, Anne (OUP Oxford, 2004)
Digressive Voices in Early Modern English Literature looks afresh at major nondramatic texts by Donne, Marvell, Browne, Milton, and Dryden, whose digressive speakers are haunted by personal and public uncertainty. To digress in seventeenth-century England carried a range of meaning associated with deviation or departure from a course, subject, or standard. This book demonstrates that early modern writers trained in verbal contest developed richly labyrinthine voices thatcaptured the ambiguities of political occasion and aristocratic patronage while anatomizing enemies and mourning personal los.